Performance of binary accelarator system on natural rubber compound - Ihda Novia Indrajati; Indiah Ratna Dewi (Majalah Kulit, Karet, dan Plastik, 2018)
Accelerator system provides different response onto the rubber compound, and in turn influences its final properties. Accelerators, such as 2,2'-Dithiobis (benzothiazole) (MBTS), N-Cyclohexylbenzothiazole-2-Sulfenamide (CBS) and diphenyl guanidine (DPG), has been selected for the study. Response of paired accelerator, MBTS/DPG and CBS/DPG in various ratio, on natural rubber (NR) compound was evaluated. Rheological properties and cure characteristics of the compounds were analyzed using Mooney viscometer and moving die rheometer (MDR) typically. Results findings showed that incorporation of DPG into the system has increased the viscosity of the compound and effected the molecular weight during the process. Further, the addition of DPG also shortened the induction period by reducing the scorch time (ts2) and decreasing the cure time (t90). Binary paired accelerator resulted in poor flow characteristic as a result of strong domination of elastic element. In general, the CBS-based system provided more balance characteristic than those of MBTS-based.